The Storms of Denali - O'Connell, Nicholas (Book collections on Project MUSE., 2012)
Reaching 20,320 feet into and above the clouds, the peak of Denali is the highest and coldest summit in North America. In this novel of adventure, adversity, and ambition by renowned mountaineer and writer Nicholas O'Connell, four men set out to conquer it. Among the sharply drawn team members is narrator John Walker, a family man trying to choose between domestic stability and mountaineering's uncertain glory. In the course of their ascent the group battles avalanches, fierce winds, and mind-numbing cold before their bond begins to splinter, leading inexorably to tragedy. Throughout the book,